Effect of Pd2+ co-doping on the structural and optical properties of Mn2+:ZnS nanoparticles. (October 2020) - Kavi Rasu, K.; Sakthivel, P.; Prasanna Venkatesan, G.K.D.
Highlights: Pd 2+ codoped Mn 2+ :ZnS nanoparticles were successfully synthesized by a simple coprecipitate technique. Structural, Morphological and optical properties were well investigation. Improvement in transmittance percentage and red shift of absorbance band were observed in UV–Visible analysis. PL spectrum of Pd 2+ doped Mn 2+ :ZnS exhibits strong red emission. Abstract: Pd 2+ (x = 0, 0.02 and 0.04) co-doped with Zn0.98-x Mn0.02 S (Mn 2+ :ZnS) nanoparticles were successfully synthesized by a simple co-precipitation method. The influence of the Pd 2+ on the structural and morphological was investigated using the powder X-ray diffraction (XRD) pattern and Scanning Electron Microscopes (SEM) and Transmission Electron Microscopes (TEM) images. XRD pattern proved the formation of the single-phase cubic structure for the Pd 2+ (x = 0, 0.02 and 0.04) co-doped Mn 2+ :ZnS samples. The average particle size of the Mn 2+ :ZnS samples were identified to be 1.75 nm from the XRD results. Fourier transform infrared (FTIR) spectra confirm the presence of vibrational modes of the ZnS with Mn 2+ and Pd 2+ ions in the samples. Red shift of the absorption band was observed and the 40% enhancement in the optical transmittance behavior was estimated for the Pd 2+ co-doped Mn 2+ :ZnS samples in the UV–Visible analysis. Photoluminescence (PL) emission spectra exhibit increased intensity in the visible region and decrease in the UV region for the Pd 2+ co-doped Mn 2+ :ZnS samples and these improved behavior of the samples were highly preferable for the optical device applications.